Stem Cell Technology: A Promising Panacea of 21th Century - Amgain, Kapil; Sajed, Ahmad Naeem (Journal of Karnali Academy of Health Sciences, 2020)
Stem cell technology is an advancement of regenerative medicine, and has proven to have infinite potential and can be a single solution of several chronic and incurable diseases. Although there are some ethical issues2, researches on embryonic stem cell argue that there is possibility of organ transplantation into the diseased person to get rid of the disease permanently. Understanding this fact of possible use of stem cell technology in near future, many countries have already started to preserve umbilical cord, even Indian Government had started the service of Cord banking Service since 2014. History of stem cell research date back to 19th century. Scientists were able to clone Tadpole in 1952, and cloned carp (named Tong Dizhon, was the world’s first cloned fish) in 1963. Similarly, Steen Willadsen had cloned Sheep from the early embryonic cells in 1996, and from somatic cells in 1997 (named it Dolly, first cloned mammal). In the same way, scientist had successfully cloned the Rhesus Monkey, Cat, Mule, etc.6 First cloned water buffalo was Samrupa in 2009 at Karnal National Diary Research Institute in India. With the evidence from successful cloning even in higher mammals from embryonic as well as somatic cell, scientists were more interested in human stem cell research and became successful to regenerate healthy tissues in diseased organs and thus can revive the person from deadly degenerative diseases. Utilizing the principle of stem cell research, scientists were able to perform bone marrow transplant in 1970.